Hydrodynamic behavior of wrapped coil water heater tank. (1st December 2020) - Elatar, Ahmed; Nawaz, Kashif; Shen, Bo; Baxter, Van
Highlights: Heat Pump Water Heater System is a modern technology which is more efficient that typical water heaters. Water tank hydrodynamic behavior during charging/discharging is very important in maintaining thermal stratifications. The influence of turbulent flow characteristics on the tank hydrodynamic behavior. Abstract: A numerical investigation using computational fluid dynamics (CFD) has been carried out to analyze the thermal behavior of a water tank integrated to a heat pump water heating system (HPWH). The heat pump condenser is a long coil wrapped around the water tank and insulated from outside from which heat is transferred from the heat pump cycle into the water stored inside the tank. The simulated water tank has a capacity of about 170 L with the charging inlet located at the bottom segment of the tank and the discharging outlet located at the top segment of the tank like commercially available water heaters. The tank was simulated during charging/discharging process with isothermal boundary condition at the tank wall to represent the majority of the process for refrigerant condensation inside the heat pump condenser (excluding superheated and sub-cooled section). Three flow rates were selected to represent low, medium and high flow pattern. Both mean and turbulent flow properties were calculated and analyzed. Heat transfer mechanisms inside the tank are quantified by calculating Richardson and Péclet numbers to show the relative contribution of driving forces. The calculations show that advection is dominant over diffusion. Mixing factor is calculated and presented. It is found that the rate of increase of mixing is nonlinear with the increase in flow rate. Mixing increased by a factor of four when the flow rate increased by a factor of two.